Population of Bemisia tabaci and Incidence of Yellow Disease in Chili Intercropped with Corn - Yolanda, Kiki; Witjaksono, Witjaksono; Putra, Nugroho Susetya (Universitas Gadjah Mada, 2024)
Bemisia tabaci is one of the limiting factors in chili farming, because it can cause damage both directly and indirectly as a vector for the Pepper yellow leaf curl virus (PepYLCV). Intercropping chili with corn is one of the efforts to control B. tabaci. Physically, corn plants are able to withstand the presence of B. tabaci, in addition to producing volatile compounds that are repellent to B. tabaci. This research was conducted to determine the optimal age of corn plants to be intercropped with chili plants. The research was conducted in Pleret District, Bantul Regency by testing five different ages of corn: 2 weeks after planting, 6 weeks after planting, 8 weeks after planting, 10 weeks after planting and control (without intercropping with corn). Weeks after planting are counted from the first day the corn seeds were planted. Yellow sticky trap (YST) was used to determine the presence of B. tabaci population in each treatment plot. YST was tied to bamboo sticks and placed on treatment beds with as many as 2 (two) traps per treatment plot. The distance between the yellow sticky trap and the plant was 30 cm, so the height of the trap was always adjusted according to the height of the plant. Observation of B. tabaci population was carried out every 5 days by counting the number of B. tabaci caught in yellow sticky traps. The results showed that the population of B. tabaci in the chili plots intercropped with corn was lower than that in the control plot, especially at the age of 6 weeks after planting (WAP). However, the intercropping of chilies and corn had no significant effect on the incidence of yellow disease in chilies.